The Influence of Human Resource Development on Performance Through Competence and Work Motivation to the Head of Mekaar Unit PT Permodalan Nasional Madani - Sallamanda, Vickry Reza; Safaria, Siti (Formosa Journal of Sustainable Research, 2024)
The purpose of this research is to determine the effect of human resource development on motivation, the effect of human resource development on competence, the effect of human resource development on performance, the effect of motivation on performance, the effect of competence on performance, the effect of human resource development on performance  through motivation as intervening variable, the effect of human resource development on performance through competence as  intervening variable. This research uses a quantitative methodology with purposive sampling method through the distribution of questionnaires to 150 respondent, analyzed using SmartPLS. The results of this study indicate that human resource development has a positive effect on motivation, human resource development has a positive effect on  competence, human resource development has a positive effect on performance, motivation has a positive effect on performance, competence has a positive effect on performance, human resource development has a positive effect on performance through motivation as intervening variable, human resource development has a positive effect on the performance through competence as intervening variable